2023
DOI: 10.1039/d2cp05083h
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian chemical reaction neural network for autonomous kinetic uncertainty quantification

Abstract: Chemical reaction neural network (CRNN), a recently developed tool for autonomous discovery of reaction models, has been successfully demonstrated on a variety of chemical engineering and biochemical systems. It leverages...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…It is the goal of this work to extend the CRNN with a Bayesian framework to increase its utility in QSP and other scientific domains. This is similar to the work by Li et al in which they also extend the CRNN to include a Bayesian framework [5], but here we use a different methodology for sampling the posterior.…”
Section: Introductionmentioning
confidence: 78%
“…It is the goal of this work to extend the CRNN with a Bayesian framework to increase its utility in QSP and other scientific domains. This is similar to the work by Li et al in which they also extend the CRNN to include a Bayesian framework [5], but here we use a different methodology for sampling the posterior.…”
Section: Introductionmentioning
confidence: 78%
“…Although PINNs and further kinetic ML approaches were previously introduced, ,, it should be noted that the influence of external parameter variation was not taken into detailed account. However, reaction optimization requires a sufficient sampling of the parameter space, such that the benefits of the previous models for process design concepts are limited .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of such probabilistic approaches, the resulting calculations also provide reasonable estimates for the uncertainty of the kinetic outcomes. 59 PINNs were also used for the detection of unknown chemical pathways and the inference of rate constants from experimental data. It has to be noted that the corresponding approaches mainly focus on activation energies in combination with standard Arrhenius kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainty quantification is an important aspect of modeling a chemical reaction, because it ensures that the model is reliable and accurate in further applications. Li et al developed Bayesian CRNN (B-CRNN) based on the deterministic CRNN and Bayesian inference, where the physical parameters (network weights) are given probabilistic distributions instead of being set as deterministic. The case studies demonstrated that the B-CRNN can simultaneously infer the chemical reaction pathways from measured noisy concentration data and perform uncertainty quantification of the identified reaction pathways, kinetic parameters, and concentration predictions with unseen initial conditions.…”
Section: The Application In Modeling Chemical Processesmentioning
confidence: 99%